15.5k views
5 votes
Solve for j.
j/-2 + 7= - 12

User FcoRodr
by
5.8k points

1 Answer

1 vote

Answer:

j = 38

Explanation:

Solve for j:

7 - j/2 = -12

Put each term in 7 - j/2 over the common denominator 2: 7 - j/2 = 14/2 - j/2:

14/2 - j/2 = -12

14/2 - j/2 = (14 - j)/2:

(14 - j)/2 = -12

Multiply both sides of (14 - j)/2 = -12 by 2:

(2 (14 - j))/2 = -12×2

(2 (14 - j))/2 = 2/2×(14 - j) = 14 - j:

14 - j = -12×2

2 (-12) = -24:

14 - j = -24

Subtract 14 from both sides:

(14 - 14) - j = -14 - 24

14 - 14 = 0:

-j = -14 - 24

-14 - 24 = -38:

-j = -38

Multiply both sides of -j = -38 by -1:

(-j)/(-1) = 38

(-1)/(-1) = 1:

Answer: j = 38

User Pseabury
by
6.3k points